Respuesta :

[tex]\textbf{Hello There!}[/tex]

Here's a step-by-step explanation!

[tex]\textbf{Step 1:}[/tex] [tex]\textbf{Simplify both sides of the equation.}[/tex]

[tex]3(a+1.5)=-1.5[/tex]

[tex](3)(a)+(3)(1.5)=-1.5 \textbf{ (distribute)}[/tex]

[tex]3a+4.5=-1.5[/tex]

[tex]\textbf{Step 2: Subtract 4.5 from both sides.}[/tex]

[tex]3a+4.5-4.5=-1.5-4.5[/tex]

[tex]3a=-6[/tex]

[tex]\textbf{Step 3:}[/tex] [tex]\textbf{Divide both sides by 3.}[/tex]

[tex]\frac{3a}{3} =\frac{-6}{3} [/tex]

[tex]a=-2[/tex]

[tex] \textit{Hopefully, this helps you!!}[/tex]

[tex]\boxed{\text{Sokka}}[/tex]